Impact of Nanosilver and Nanocopper on Antifungal Properties of Plastic Elements in the Aspect of Their Use in Agri-Food Processing (Agricultural Engineering, 2018)
The paper presents results of microbiological research of plastic elements. Plastic elements were made of the polystyrene composition with addition of nanosilver and nanocopper with a laboratory extruder EHP 25ELine. Microbiological research was carried with regard to evaluation of antifungal impact of nanoadditives according to international standards with Cryobank (Mast Diagnostica). A positive impact of nanoadditives on antifungal properties of polystyrene elements produced by means of extrusion which is very favourable in the aspect of their use in agri-food processing.